Effect of calcium and vitamin D supplementation on serum calcium level in children with idiopathic nephrotic syndrome - Vaya Dasitania; Alex Chairulfatah; Dedi Rachmadi (Indonesian Pediatric Society, 2014)
Background Patients with idiopathic nephrotic syndrome (NS) maydevelop hypocalcemia caused by low levels of albumin and vitaminD -binding protein, which subsequently decreases calcium absorptionin the intestine. Hypocalcemia may result in neuromuscularmanifestations, such as Chvostek's and Trosseau's signs.Objectives To evaluate the effect of calcium and vitamin Dsupplementation on hypocalcemia and its clinical manifestationsin idiopathic NS children.Methods A randomized, single-blind, controlled trial wasperformed in idiopathic NS patients aged 1-14 years. Subjectswere divided into treatment and placebo groups. Subjects inthe treatment group received 800 mg elemental calcium and400 IU vitamin D supplementation, while they in control groupreceived placebo syrup, both for 8 weeks. Serum calcium andmanifestations of hypocalcemia were examined before and aftersupplementation.Results Thirty subjects completed the study (15 in each group).Seventeen subjects experienced hypocalcemia. Chvostek's andTrosseau's signs were observed in 6 subjects in the treatment groupand 2 subjects in the placebo group (P= 0.427). After 8 weeks ofintervention, Chvostek's and Trosseau's signs disappeared in bothgroups, and calcium levels were significantly increased in bothgroups compared to the levels before intervention. However, therewas no significant difference in serum calcium levels after 8 weeksbetween the treatment and placebo groups (P =0.707).Conclusion Normalization of serum calcium levels and improvedclinical manifestations ofhypocalcemia occur both in NS patientswho receive calcium and vitamin D supplementation and thosewho do not.